15H-Diindolo[2, 3-b:1′, 2′, 3′-lm]carbazole: a novel rigid donor for highly efficient thermally activated delayed fluorescence emitters. Issue 26 (11th June 2019) - Konidena, Rajendra Kumar; Lee, Kyung Hyung; Lee, Jun Yeob; Hong, Wan Pyo
Abstract : A novel rigid and strong 15 H -diindolo[2, 3- b :1′, 2′, 3′-lm]carbazole (DICz) donor was developed for efficient green thermally activated delayed fluorescence emitters and demonstrated promising device performance with EQE exceeding 20%. Abstract : In this contribution, we report a novel rigid 15 H -diindolo[2, 3- b :1′, 2′, 3′-lm]carbazole (DICz) donor for designing efficient thermally activated delayed fluorescence emitters named 2-(15 H -diindolo[2, 3- b :1′, 2′, 3′-lm]carbazol-15-yl)-5-(4, 6-diphenyl-1, 3, 5-triazin-2)benzonitrile (DICzCNTrz ) and unravelled its effects on the physicochemical and electroluminescence properties by comparing it with the control molecule, 2-(9 H -carbazol-9-yl)-5-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)benzonitrile (CzCNTrz ) featuring a carbazole donor. The photophysical properties revealed that theDICzCNTrz showed small singlet–triplet energy splitting, short delayed fluorescence exciton lifetime and high photoluminescence quantum yield when compared toCzCNTrz . The organic light emitting diode fabricated using theDICzCNTrz -based emitter exhibited superior performance with EQE of 21.4% and reduced efficiency roll-off at high brightness when compared to the device with theCzCNTrz -based emitter, which showed maximum EQE of 13.9%.